Dissociative Convulsions Mimicking Epileptic Seizures: A Diagnostic Challenge in a Patient with Complex Psychosocial Stressors - Ardita Da’imah Cahyani; Era Catur Prasetya (Galen: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Dissociative convulsions are paroxysmal events resembling epileptic seizures yet occurring without ictal epileptiform activity, and they are frequently misdiagnosed or delayed, especially in resource‑limited settings. This study aims to describe the diagnostic process, clinical course, and psychosocial context of dissociative convulsions in a 29‑year‑old woman with complex psychosocial stressors, and to illustrate a structured management approach. The research adopted a qualitative case study design, employing a descriptive‑analytic paradigm and inductive analysis. Data were collected from a single case meeting the criteria for dissociative convulsions (F44.5), evaluated in a psychiatric outpatient setting, through comprehensive clinical interviews, mental status examination, behavioral observations, and documentation of semiotic seizure features, alongside routine EEG, CT head, and laboratory tests. Data were analyzed thematically by identifying patterns of semiotics, psychosocial triggers, and treatment response. The result shows that seizure‑like episodes emerged in close temporal relation to interpersonal conflict and reproductive losses, were accompanied by prominent autonomic symptoms, and occurred against a background of adverse childhood experiences and borderline‑type personality traits. The conclusion highlights that a careful semiotic assessment, normal ancillary investigations, and thorough psychosocial evaluation support the diagnosis of dissociative convulsions, even without video‑EEG monitoring, and that a multimodal biopsychosocial strategy combining psychoeducation, cognitive‑behavioral therapy, grounding techniques, and pharmacotherapy effectively reduces seizure frequency and psychosocial impairment.